Reconstruction of Environmental Fiqh Language Based on Tazkiyatun Nafs: a Sufistic Approach to Students' Mental Health - Muhammad Amiruddin (Global Journal of Islamic Education, 2026)
This study proposes the construction of environmental fiqh language within Islamic boarding schools (pesantren) as an integrative framework to shape Generation Z characterized by tazkiyatun nafs, Sufi orientation, and psychological well-being. Employing a qualitative interpretative approach with a multi-site design across several pesantren in Indonesia, data were collected through limited participatory observation, semi-structured interviews, and document analysis. The data were analyzed using thematic-critical and religious discourse analysis. The findings demonstrate that eco-theological language in pesantren operates as a semiotic-performative system that not only transmits theological knowledge but also internalizes ecological values through daily practices. The integration of tawhid, environmental ethics, and spiritual practices fosters faith-based ecological awareness while strengthening students' self-regulation and emotional stability. The novelty of this study lies in formulating environmental fiqh language as a psycho-spiritual eco-systemic model that integrates linguistic, theological, and mental health dimensions into a coherent analytical framework. This model positions pesantren as a living laboratory for developing sustainability ethics grounded in Islamic spirituality. The study contributes to the advancement of pesantren-based eco-theosophy and offers an alternative paradigm in global sustainability discourse rooted in transcendental values.